Salicylic acid and sowing dates effect on linseed (Linum usitatissimum) under rainfed rice fallow condition - BONIA, DIPSIKHA; SARMAH, ANJAN KRISHNA; RAFIQUE, N T; DUTTA, MARAMI; DAS, SANGITA (The Indian Journal of Agricultural Sciences, 2026)
A field experiment was conducted during the rabi season of 2022–23 at ICR Farm of Assam Agricultural University, Jorhat to assess the effect of salicylic acid on rainfed late sown linseed (Linum usitatissimum L.) under different sowing dates in rice fallow condition. The experiment was laid out in split-plot design with three sowing dates in main plot and four salicylic acid concentrations in sub plots. Different sowing dates and salicylic acid concentrations significantly affected the growth and yield of linseed. Although sowing on 20th November was most favourable for linseed growth and yield, application of salicylic acid at 100 ppm at pre-flowering and seed ball formation stage improved crop performance even under late sowing condition. Thus, salicylic acid application at 100 ppm may be recommended as a crop management strategy to mitigate the effects of delayed sowing of linseed in rainfed rice-fallow condition.